Pembangunan dan Pemberdayaan Masyarakat Desa melalui Pelatihan Pengelolaan Sumber Daya pada Badan Usaha Milik Desa (BUMDes) Desa Uiasa Kecamatan Semau Kabupaten Kupang - Samin, Mikael; Hasan, Muhammad Husain; Sukmawati, Sukmawati; Andrinata, Andrinata (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
The implementation of Village-Owned Enterprises has not been fully implemented by all villages in Indonesia in accordance with Law No. 6/2014. This activity intends to provide training for managers of Village-Owned Enterprises in Uiasa Village, Semau District, Kupang Regency. Data collection methods are Focus Group Discussion (FGD), unstructured interviews. The results of the activity show that the management of resources carried out by the Uiasa Village-Owned Enterprises is not optimal so that assistance will be carried out to strengthen the organizational structure and accelerate the potential of the economic sectors it manages.